STUDI SOSIOLOGIS TENTANG MODAL SOSIAL PADA PAGUYUBAN PERSAUDARAAN JAWA KUANTAN SINGINGI (PERJASING) - Puspito, Hendro; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
cle of Brotherhood Java Kuantan Singingi is a community organization of Java that is born of a sense of concern for the growing conditions at the time, where ethnic non- ethnic local pressure and unpleasant treatment while waiting for the bus or buy a ticket for travel undertaken by elements that responsible. Fraternal Society organizations Kuantan Java Singingi which until now still exists. Fraternal Society of Java Kuantan Singingi was confirmed in 2006 in the village of Gold Water District of Singingi Regency Kuantan Singingi bersempena on the anniversary of the disesa Transmigration decided. Fraternal Society of Java Kuantan Singingi formed because they are aware that humans require the help of others to meet their needs. Fraternal Society of Java Kuantan Singingi a community that still exists today in the area Kuntan Singingi .This research was conducted to find out what social capital embodied in Kuantan Java Singingi Brotherhood Society . This research was conducted using qualitative method by using purposive technique dimanana research subjects consist of a chairman, deputy chairman, secretary and members of the Brotherhood Society Singingi Kuantan Java. In the Java community, they have a high respect for those considered above. Cohesiveness and solidarity of the social capital that can facilitate a search for a common vision and mission. Social capital embodied in very diverse activities such as sponsorship of orphans, economic empowerment and a member of the Islamic new year peringgatan ( suroan ). The existence of social capital in the Society Brotherhood Singingi Kuantan Java is one of the main components in moving togetherness, solidarity, trust and interrelatedness interrelatedness mengguntungkan to achieve common goals.Keywords: Social Capital, Society, Social Activities